Kinetic investigation of the asymmetric hydrogenation of benzylphenylephrone in continuous flow: enabling R&D with flow chemistryand microfluidics - Moll, Maurice; Wängler, Björn; Wängler, Carmen; Röder, Thorsten (Chimia, 2025)
In the pharmaceutical industry, efficient, fast, and cost-effective API manufacturing processes are crucial for maintaining competitiveness. However, traditional production methods are often dominated by multi-purpose batch processes and empirical development approaches. This study presents the design and development of a fully automated, mL-scale continuous flow process for the asymmetric hydrogenation of benzylphenylephrone to (R)-benzylphenylephrine (BPE). The process employs a rhodium-based homogeneous catalyst under high pressure (up to 65 bar), achieving conversions of >96%, yields of up to 95% and high enantiomeric excess (ee) of up to 91%, with residence times of less than five minutes and a molar substrate to catalyst ratio (S/C) of 750. Kinetic investigations were conducted in a continuous flow microreactor, resulting in the development of a kinetic model that closely matches experimental data.
Gesehen am 02.10.2025